SISTEM INFORMASI MANAJEMEN DANA DONATUR BERBASIS WEB PADA PANTI ASUHAN YATIM MADANI - Sampurna Dadi Riskiono; Fikri Hamidy; Tami Ulfia (Universitas Teknokrat Indonesia, 2020)
Yatim Madani Orphanage does not yet have an integrated information system to support its data processing, for example data management for orphans and assistance. The process that has been carried out so far is still manual, such as recording data in books, and delivery of fund information, the institution only tells when there are donors visiting the Orphanage. From this research a website-based Donor Fund Management Information System is designed using crowdfunding method, with a donation site model that disseminates donation information through social media making it easier to make donation projects and publish funds needed